To map the Island of Bourbon in the XVII-XIXth century: Cartographical travel in the one of the four of the main islands from Africa seas, Bourbon Lontan - (:unkn) unknown (My University, 2010)
This article examines the cartographical history of the Island of Bourbon through the study of three predominant maps representing various stages in a process which led, in the nineteenth century, to a scientifically complete representation of the contours of this island. Leaving aside the positivist conception of the history of mapping but without ignoring the impact of European metropoles in their rewriting, or in the imposition of cartographical models, this study reveals both the ebb and flow and possible bifurcations in the interpretation of cartographical data. Each of the documents enables the analysis of the material problems and conceptual questions related to the mapping of an area that was still physically difficult to reach. The text aims to highlight the modalities which existed (either particular to each map or those held in common) so as to point to the various historical processes that were engaged in the charting of Africa and Bourbon.
Keywords: African Research